The Alabama Revisited: Some Observations on the Evolution of Rights and Duties of Neutral States in Armed Conflicts under International Law - Połatyńska, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The paper discusses the concept of neutrality in contemporary international law. The traditional notion of neutrality, stemmed from states’ practice since the 17th century, means the particular status, defined by international law, of a state that is not party to an armed conflict. The basic premise of this notion is, in short, quite straightforward: on the one hand, the neutral state has the right to remain apart from, and not to be adversely affected by, the conflict. On the other hand, the neutral state is under the obligation of non-participation and impartiality. In the 20th and 21st centuries, however, following several treaties and modifications of states’ practice on that matter, the law of neutrality underwent changes and introduced new concepts, e.g. qualified neutrality or non-belligerency. This change, however, has produced only modifications of specific rules of the law of neutrality, not a general abolition of this whole body of law.